Farmers perceptions on the application of climate change adaption strategy : a case study of small scale maize farmers in Ward 27 of the Greater Giyani Local Municipality, Limpopo, South Africa - Mkansi, Ntlharihani Deon (My University, 2024)
The agricultural sector in South Africa plays an essential role in promoting rural development, reducing poverty, and ensuring food security. However, climate change poses a significant challenge to agriculture, impacting water availability, food supply stability, and overall ecosystem health. To address these concerns, adaptation strategies such as adjusting planting schedules and employing soil and water conservation practices are increasingly seen as vital for the long-term sustainability of farming operations. Although these strategies are well-documented globally, there is limited research on their implementation and perceived effectiveness among small- scale maize farmers in specific South African regions, such as ward 27 of the Greater Giyani Local Municipality in Limpopo Province. The study's aim was to explore small-scale maize farmer’s perception on the application of climate change adaptation strategies in ward 27 of the Greater Giyani Local Municipality, Limpopo Province, South Africa. The first objective of the study was to profile the socio-economic characteristics of small-scale maize farmers in Ward 27 of the Greater Giyani Local Municipality, Limpopo Province. The second objective was to evaluate the small-scale maize farmers perception on the application of climate change adaptation strategies in the study area and the third objective was to determine factors influencing the small-scale maize farmers perception on the application of climate change adaptation strategies in the study area. Data was collected from 130 small-scale maize farmers using snowball sampling technique. Descriptive statistics results showed that the average age of the farmers was 57 years. Approximately 61% of the small-scale maize farmers in Ward 27 of Greater Giyani local Municipality were female and 39% were male. The study identified strategies used by small-scale maize farmers to enhance the risks of climate change. The most dominant strategy adopted was crop diversification (32.4%), followed by changing planting times (19.4%). Farmers also practiced efficient water management, including rainwater harvesting (12.6%) and improved irrigation methods (14.6%). Additionally, 10.7% used climate-resilient crop varieties. Other practices included adjusting plant spacing and pest control (3.2%) and applying mulching, composting, and organic manure (7.1%) to maintain soil fertility. The least-adopted strategy was other practices such as adjusting plant spacing and pest control. vi To fulfil the second objective, a Likert scale along with descriptive statistics were employed to evaluate the perceptions of small-scale maize farmers regarding climate change adaptation strategies. Findings showed that about 55.1% of the farmers held positive views about the perceptions of the application of climate change adaptation strategies whereas 33.2% expressed negative perceptions. Additionally, 11.7% of the farmers were uncertain about the effectiveness or feasibility of implementing these adaptation strategies. Lastly, a Binary logistic regression model was applied to analyse the factors influencing small-scale maize farmers' perceptions of climate change adaptation strategies. The results from this model indicated that several variables significantly impacted these perceptions in Ward 27 of the Greater Giyani Local Municipality. Key factors included marital status, employment status, access to weather forecast information, and membership in farmers' cooperatives. Based on empirical findings, it is suggested that the government enhance access to weather forecast information, improve employment opportunities for small-scale farmers, and strengthen access to farmer cooperatives to support climate resilience in agriculture. Improving the dissemination of accurate weather forecasts through local agricultural extension services and mobile technology can help farmers make informed decisions, thereby reducing vulnerability to climate variability. Additionally, launching targeted programs for employment in climate-resilient agricultural strategies and providing training in sustainable techniques can promote job creation and investment in adaptation strategies. Finally, encouraging the formation of agricultural cooperatives can facilitate collective bargaining and resource sharing, enabling farmers to adopt climate-smart practices more effectively. These recommendations are consistent with national strategies designed to improve food security, alleviate poverty, and promote sustainable livelihoods in response to climate change.
Thesis (M. Sc. Agriculture (Agricultural Economics)) -- University of Limpopo, 2025
Keywords: Climate change; Perception; Adaptation strategies; Small-scale maize farmers; Farmers - South Africa -- Limpopo; Farms, Small; Climatic changes; Climatic changes -- Risk assessment -- South Africa -- Limpopo